Prevalence and influencing factors of reduced visual acuity among young children in Changning District， Shanghai - JIANG Zihan; ZHUANG Jianlin; JIANG Ting’an; NIU Chunjin (Shanghai yufang yixue, 2024)
ObjectiveTo analyze the prevalence of reduced visual acuity of young children in Changning district of Shanghai and to explore the influencing factors， so as to provide a reference basis for formulating prevention and control measures for children’s reduced visual acuity.MethodsVisual acuity examination and questionnaire survey were conducted on 5 772 middle class children in kindergartens and first grade children in primary schools who participated in the refractive screening in Changning District in 2019. χ2 test and logistic regression analysis were used to explore the influencing factors of reduced visual acuity.ResultsThe overall prevalence of reduced visual acuity among lower-aged children was 10.4% （596/5 772）. The prevalence of reduced visual acuity in the first grade children was 10.1% （284/2 822）， and that in the middle class children of kindergarten was 10.8% （312/2 900）. The prevalence of reduced visual acuity was 10.2% （298/2 933） in boys and 10.7% （298/2 789） in girls. 98.1% of young children had one or more bad habits when using eyes. Multivariate logistic regression analysis showed that frequent excessive head lowering （OR=1.713） and sometimes too close to the screen （OR=1.294） were independent risk factors for reduced visual acuity in young children； After stratification by age， frequent excessive head lowering （OR=1.997） increased the risk of reduced visual acuity of children in the first grade of primary school. Premature birth （OR=1.841）， sometimes excessive head lowering （OR=1.363） and frequent excessive head lowering （OR=2.002） increased the risk of reduced visual acuity of children in the middle class of kindergarten.ConclusionFor young children， we should pay more attention to their daily eye use distance， correct their bad behaviors for using eyes such as excessively lowering their head when using eyes and too close to the video screen when using electronic products， so as to prevent and delay the occurrence and development of reduced visual acuity.